2001
DOI: 10.3748/wjg.v7.i1.66
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bowel rehabilitative therapy on structural adaptation of remnant small intestine: animal experiment

Abstract: AIM To investigate the individual and the combined effects of glutamine, dietary fiber, and growth hormone on the structural adaptation of the remnant small bowel. METHODS Forty-two adult male SpragueDawley rats underwent 85% mid-small bowel resection and received total parenteral nutrition ( T P N ) s u p p o r t d u r i n g t h e f i r s t t h r e e p o s t o p e r a t i o n a l d a y s . F r o m t h e 4 t h postoperational day, animals were randomly assigned to receive 7 different treatments for 8 days: TPN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 39 publications
(37 reference statements)
0
37
0
Order By: Relevance
“…Combination of glutamine, human recombinant growth hormone has been shown to influence bowel adaptation [19][20][21][22][23][24] . The study by Byrne et al [25,26] indicated that at one year of follow-up 40 % of treated patients were able to reduce or discontinue parenteral nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Combination of glutamine, human recombinant growth hormone has been shown to influence bowel adaptation [19][20][21][22][23][24] . The study by Byrne et al [25,26] indicated that at one year of follow-up 40 % of treated patients were able to reduce or discontinue parenteral nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are no reports of research studying the biodistribution of radiopharmaceuticals after surgical procedures. In the present study, we used an experimental model of massive resection of the small intestine, characterizing the short bowel syndrome, which results in unsuitable water and nutrient absorption, causing malnutrition 9,10 . In spite of the short bowel syndrome, the intestine can be adapted through physiologic, cellular and moleculares mechanisms 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, glutamine has greater effects on the ileum, which has moved more proximally after the resection, than on the jejunum (25). After massive intestinal resection, the distal intestines are brought to a more proximal position and thus the increase in intestinal adaptation capacity becomes clearer as they encounter glutamine earlier (26,27). The resection was deliberately applied in the region of the proximal jejunum, where the small intestine proximal passage is fast and absorption is low.…”
Section: Discussionmentioning
confidence: 99%